Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-10-11T18:15:20+02:00
B= (3x + 4)² - 81
B= 9x² + 24x + 16 - 81
B= 9x² + 24x - 65

B= (3x + 4)² - 81
B= (3x + 4)² - 9²
B= (3x + 4 - 9)(3x + 4 + 9)
B= (3x - 5)(3x + 13)

Pour x = - 5

B= (3 x (- 5) - 5)(3 x (- 5) + 13)
B= (- 15 - 5)(- 15 + 13)
B= - 20 x (- 2)
B= 40

Pour x = 5/3 :

B= (3 x 5/3 - 5)(3 x 5/3 + 13)
B= (15/3 - 5)(15/3 + 13)
B= (15/3 - 15/3)(15/3 + 39/3)
B= 0 x 54/3
B= 0
-------------------------------------------------
F= (3x - 5)² - (3x - 5)(x + 4)
F= 9x² - 30x + 25 - (3x² + 12x - 5x - 20)
F= 9x² - 30x + 25 - 3x² - 12x + 5x + 20
F= 6x² - 37x + 45

F= (3x - 5)² - (3x - 5)(x + 4)
F= (3x - 4)(3x - 5 - x - 4)
F= (3x - 4)(2x - 9)

Pour x = 1

F= (3 x 1 - 4)(2 x 1 - 9)
F= (3 - 4)(2 - 9)
F= - 1 x (- 7)
F= 7

Pour x = 4,5

F= (3 x 4,5 - 4)(2 x 4,5 - 9)
F= (13,5 - 4)(9 - 9)
F= 9,5 x 0
F= 0